The complete mitochondrial genome of West Indian drywood termite, Cryptotermes brevis (Walker) (Isoptera: Kalotermitidae) - He, Peishan (Mitochondrial DNA B Resour, 2019)
The complete mitogenome of Cryptotermes brevis (Walker) (Isoptera: Kalotermitidae) is confirmed. This circular mitogenome (accession number MK618724) length is 15,674 bp, containing 13 protein-coding genes, 2 rRNA genes, and 22 tRNA genes. The overall G + C proportion is 31.48%. These data expand the termite mitogenome databases, provide data support for the next phylogenetic and evolutionary studies.